Pirates? The Politics of Plunder, 1550-1650 - Jowitt, Claire. author. aut Link
XIII, 244 p.
Keywords: This book provides an insight to the cultural work involved in violence at sea in this period of maritime history. It is the first to consider how 'piracy' and representations of 'pirates' both shape and were shaped by political, social and religious debates, showing how attitudes to 'piracy' and violence at sea were debated between 1550 and 1650.